Corrosion-resistant hydrophilic easy-to-clean coating and preparation method thereof
By adding specific ingredients and process treatment to inorganic hydrophilic coatings, the problem of poor hydrolysis and poor coating performance of coatings in humidity environment is solved, and higher water resistance, salt -resistant performance and coating are achieved sex.
Patent Information
- Application Number
- CN202310880449.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-18
AI Technical Summary
The existing inorganic hydrophilic coatings are prone to hydrolysis and cracking in humid environments, and have poor coating performance on non-smooth surfaces, making it difficult to maintain corrosion resistance on metal surfaces such as galvanized plates.
Use 20-60 parts of water, 30-50 parts of potassium silicate, 1-8 parts of potassium methyl silicate, 2-8 parts of silane oligomer, 0.2-0.6 parts of acetylene glycol polyoxyethylene ether, and 0.8 parts of butanol. , the composition is 0.5 parts of boron trifluoride monoethylamine complex, and the coating is prepared by stirring and drying at high temperature.
It improves the water resistance, salt -resistant performance and coating of the coating, which can effectively prevent hydrolysis and cracking. It is suitable for stainless steel, glass, galvanized plate and other surfaces to extend the life of the coating.
Smart Images

Figure BDA0004344354590000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of inorganic hydrophilic coatings, and in particular to a corrosion-resistant hydrophilic easy-to-clean coating and a preparation method thereof. Background Art
[0002] Hydrophilic coatings have special surface wettability. When in contact with water, they can quickly form a water film on their surface, quickly floating up the stains on the surface, thus achieving an easy-to-clean effect. Currently, they have been gradually applied to industries such as construction, photovoltaics, automobiles, and home appliances. However, due to problems such as low thickness and poor wettability of hydrophilic coatings, hydrophilic coatings can only be applied on glass and stainless steel surfaces on a large scale.
[0003] Currently, existing hydrophilic coatings have the following problems:
[0004] 1. Existing inorganic hydrophilic coatings mainly rely on potassium and sodium ions to increase hydrophilicity and are prepared using silicate materials. Silicate materials are still water-soluble after high-temperature baking, and will hydrolyze in a humid environment to form a gel that will crack after repeated wetting and drying, reducing the life of the coating. 2. Existing inorganic hydrophilic coatings are mostly suitable for high-surface-energy, smooth surfaces such as stainless steel and glass. This is due to the poor wettability caused by the high surface energy of the hydrophilic coating. 3. Because the hydrophilic material is highly hydrophilic, the material is thin, and the protection of the substrate is poor, it is easy to rust, fall off, and fail when coated on other metal surfaces such as galvanized plates and cold plates.
[0005] For example, the Chinese invention patent "Water-based long-lasting anti-fog self-cleaning coating and its preparation method" with application number 202210984728.7 discloses a water-based long-lasting anti-fog self-cleaning coating and its preparation method; it includes the following steps: placing a silicate in a reactor, adding a silane coupling agent for reaction, and then dripping a hydrolysis stabilizer, stirring to react to obtain a silane-modified silicate; placing parts of silica-alumina sol and undecylenic acid in a reactor, stirring, and initiating polymerization by ultraviolet light to obtain a silica-alumina sol; then, placing the silane-modified silicate and silica-alumina sol in a reactor and stirring, adding potassium hydroxide, and stirring until the liquid changes from milky white to transparent to obtain a product; adding the product, deionized water, silicate curing agent and wetting and leveling agent into a stirring kettle and stirring evenly to prepare a water-based inorganic long-lasting anti-fog self-cleaning coating. The paint has a long service life and good hydrophilicity, but silicate is water-soluble and will hydrolyze in a humid environment. In addition, the paint is only suitable for smooth surfaces such as glass and has poor coating ability on metal surfaces such as galvanized sheets. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide a corrosion-resistant, hydrophilic, easy-to-clean coating with good water resistance and salt spray resistance in view of the above-mentioned technical status quo.
[0007] The second technical problem to be solved by the present invention is to provide a corrosion-resistant, hydrophilic, and easy-to-clean coating with good coating properties in view of the above-mentioned technical status quo.
[0008] The third technical problem to be solved by the present invention is to provide a method for preparing a corrosion-resistant, hydrophilic, and easy-to-clean coating in view of the above technical status.
[0009] The technical solution adopted by the present invention to solve the above-mentioned first and second technical problems is: a corrosion-resistant hydrophilic easy-to-clean coating, characterized in that:
[0010] The corrosion-resistant hydrophilic easy-to-clean coating is composed of 20-60 parts of water, 30-50 parts of potassium silicate, 1-8 parts of potassium methyl silicate, 2-8 parts of silane oligomer, 0.2-0.6 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol and 0.5 parts of boron trifluoride monoethylamine complex.
[0011] Alkyne glycol polyoxyethylene ether can form an effective water-resistant molecular film on the surface of the material. The hydroxyl groups on the molecule can form hydrogen bonds with the silanol groups, making the polyoxyethylene ether attached to the surface more firmly. The hydroxyl groups can also produce at the same time with the epoxy groups on the silane oligomers. The polyoxyethylene ether greatly reduces the viscosity of the coating and can increase the leveling wettability of the coating. Due to its special molecular arrangement, the hydrophilic groups are arranged horizontally on the bubble membrane wall, and the alkyl groups are distributed farther, which will reduce the attraction between molecules, making the bubble membrane wall in a relatively unstable state and easier to break bubbles, so it can reduce the generation of bubbles in the production and processing of the coating.
[0012] Potassium methyl silicate can react with CO2 to form a waterproof and breathable film. It also has a certain potassium-fixing effect, so that potassium ions can be evenly dispersed on the outer surface of the coating to increase the hydrophilicity. However, since potassium methyl silicate and acetylene glycol polyoxyethylene ether both have hydrophobic functional groups, the amount added must be controlled, otherwise the hydrophilicity of the material will be greatly reduced.
[0013] Silane oligomers carry epoxy groups and can undergo cross-linking reactions with hydroxyl groups (silanol groups or hydroxyl groups on polyoxyethylene ether) at temperatures above 200°C, thereby increasing the overall degree of cross-linking of the material. Boron trifluoride monoethylamine complex is a latent catalyst for epoxy groups and can cure and cross-link epoxy groups with amino groups at high temperatures, thereby reducing the problem of hydrolysis of the material in the later stage and increasing the life of the material.
[0014] Since the silane oligomer has been end-capped and the catalyst is a latent catalyst, the cross-linking reaction can only be carried out at a temperature above 100 degrees Celsius. Therefore, the overall stability of the coating is strong. It can be made into a single-component coating and can maintain stability for a long time at room temperature. There is no need to prepare a two-component catalyst, and there is no need for further aging process before using the coating.
[0015] Preferably, the potassium silicate has a solid content of 35% and a modulus of 3.5.
[0016] Preferably, the silane oligomer is 3-(2,3-epoxypropyloxy)propyltrimethoxysilane oligomer.
[0017] Preferably, the solid content of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer is 30%, and the CAS number before hydrolysis polymerization is 2530-83-8.
[0018] Preferably, the polymerization degree of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer is 2-3.
[0019] The technical solution adopted by the present invention to solve the above-mentioned third technical problem is: a method for preparing a corrosion-resistant, hydrophilic, easy-to-clean coating, characterized in that: at room temperature, stirring and adding the weight parts of the aforementioned corrosion-resistant, hydrophilic, easy-to-clean coating, and then continuing to stir for 2 hours to obtain the corrosion-resistant, hydrophilic, easy-to-clean coating.
[0020] Compared with the prior art, the advantages of the present invention are: potassium methyl silicate, silane oligomer, and boron trifluoride monoethylamine complex are added, and the water resistance and salt spray resistance of the hydrophilic coating are increased by proportioning, while maintaining good hydrophilicity; and the wettability of the hydrophilic coating to the substrate is increased by adding acetylene glycol polyoxyethylene ether. The prepared coating has better bonding force and coating ability, so it can be coated on the surface of metal materials such as stainless steel plates, glass, galvanized plates, cold plates, magnesium-aluminum alloys, etc. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below with reference to the embodiments.
[0022] The reagents and equipment used in the embodiments and comparative examples are as follows:
[0023] Potassium silicate, solid content 35%, modulus 2.8-4.0;
[0024] 3-(2,3-Epoxypropyloxy)propyltrimethoxysilane; solid content 30%; CAS: 2530-83-8; degree of polymerization 2 to 3;
[0025] 1 part of acetylene glycol polyoxyethylene ether, CAS: 9014-85-1.
[0026] Example 1
[0027] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate with a modulus of 3.5, 3 parts of potassium methyl silicate, 5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.5 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0028] Example 2
[0029] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 20 parts of water, 30 parts of potassium silicate with a modulus of 3.5, 1 part of potassium methyl silicate, 2 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.2 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0030] Example 3
[0031] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 60 parts of water, 50 parts of potassium silicate with a modulus of 3.5, 8 parts of potassium methyl silicate, 8 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.6 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0032] Example 4
[0033] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate with a modulus of 2.8, 3 parts of potassium methyl silicate, 5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.5 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0034] Example 5
[0035] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate with a modulus of 4.0, 3 parts of potassium methyl silicate, 5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.5 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0036] Comparative Example 1:
[0037] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate, 5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.5 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0038] Comparative Example 2:
[0039] In a high-speed disperser at 1500 rpm and room temperature, add 40 parts of water, 40 parts of potassium silicate, 3 parts of potassium methyl silicate, 0.5 parts of acetylene glycol polyoxyethylene ether, and 0.8 parts of butanol in parts by weight; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0040] Comparative Example 3:
[0041] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate, 10 parts of potassium methyl silicate, 10 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.5 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0042] Comparative Example 4
[0043] In a high-speed disperser at 1500 rpm and room temperature, add: by weight, 40 parts of water, 40 parts of potassium silicate with a modulus of 3.5, 3 parts of potassium methyl silicate, 5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex; continue stirring for 2 hours after the addition is completed to obtain a corrosion-resistant, hydrophilic, and easy-to-clean coating. Apply the prepared coating to the surface of the galvanized sheet and dry at 210°C.
[0044] The results of testing the coatings obtained in Examples 1-5 and Comparative Examples 1-4 are shown in Table 1:
[0045] The test method for galvanized sheet coated with paint is as follows:
[0046] 1. Oil contact angle and water contact angle test: Use Shengwu 350H multi-function contact angle tester for testing; test conditions: At room temperature of 30℃, drop 0.2uL of test liquid, test at 1 / 4, 1 / 2, and 3 / 4 positions of the test sample respectively, and take the average value.
[0047] 2. Water blister test: At room temperature, put the prepared samples into different beakers at room temperature, so that the samples are in an inclined state with an angle of 75° to the horizontal plane in the beaker, and add pure water to immerse the sample to 1 / 2 of the length of the sample. Leave it to stand and observe it every 24 hours. If a large white spot of more than 2mm is found on the immersed part, it is considered to be failed, and the failure time is recorded.
[0048] 3. Neutral salt spray: Use GB10125-1997 for testing and observe every 24 hours. If corrosion (black and white rust) extends more than 2mm along the edge of the galvanized sheet, or 2mm white rust appears in the middle of the galvanized sheet, it is considered failure.
[0049] The coating properties of the coating are tested as follows:
[0050] Use the dip coating method to coat, immerse different metal samples in the coating for 1 minute, pull the sample at a speed of 10mm / s, and observe the surface sag, shrinkage, and dripping when all the samples are pulled out. After the sample is left still for 5 minutes, observe carefully. If the sample surface is smooth and has no defects, it is excellent; if there are a few sag marks (the sag marks are concentrated at 1 / 4 of the sample surface) but no shrinkage, it is good; sag marks (the sag marks are concentrated at 1 / 2 of the sample surface)
[0051] Table 1
[0052]
[0053] As shown in Table 1, the blister resistance and salt spray resistance of Examples 1-5 are higher than those of Comparative Examples 1-2, and the water contact angle and the contact angle of Examples 1-5 are lower than those of Comparative Examples 1-2; therefore, the clean coating increases the water resistance and salt spray resistance while maintaining good hydrophilicity and lipophilicity. Moreover, it can be applied to the surface of metal materials with excellent bonding and coating capabilities. By comparing Comparative Example 3, it can be seen that excessive addition of potassium methyl silicate and epoxy silane oligomers will reduce the hydrophilicity of the material, increase the lipophilicity of the material, and make the material no longer easy to clean. As shown in Example 1 and Comparative Example 4, not adding acetylene glycol polyoxyethylene ether will make the coating property worse.
Claims
1. A corrosion-resistant, hydrophilic, easy-to-clean coating, characterized by: The corrosion-resistant, hydrophilic, easy-to-clean coating is composed of the following parts by weight: 20-60 parts of water, 30-50 parts of potassium silicate, 1-8 parts of potassium methyl silicate, 2-8 parts of silane oligomer, 0.2-0.6 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex.
2. The corrosion-resistant, hydrophilic, easy-to-clean coating according to claim 1, characterized in that: The corrosion-resistant, hydrophilic, easy-to-clean coating is composed of the following parts by weight: 30-45 parts of water, 30-45 parts of potassium silicate, 2-6 parts of potassium methyl silicate, 2-6 parts of silane oligomer, 0.2-0.6 parts of acetylene glycol polyoxyethylene ether, 0.8 parts of butanol, and 0.5 parts of boron trifluoride monoethylamine complex.
3. The corrosion-resistant, hydrophilic, easy-to-clean coating according to claim 2, characterized in that: The solid content of the potassium silicate is 35%, and the modulus is 2.8-4.
0.
4. The corrosion-resistant, hydrophilic, easy-to-clean coating according to claim 3, characterized in that: The silane oligomer is 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer.
5. The corrosion-resistant, hydrophilic, easy-to-clean coating according to claim 4, characterized in that: The solid content of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer is 30%; CAS: 2530-83-8.
6. The corrosion-resistant, hydrophilic, easy-to-clean coating according to claim 5, characterized in that: The polymerization degree of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane oligomer is 2-3.
7. A method for preparing the corrosion-resistant, hydrophilic, easy-to-clean coating according to any one of claims 1 to 6, characterized in that: Under normal temperature, the corrosion-resistant hydrophilic easy-to-clean coating according to claim 1 is added in parts by weight while stirring, and then the stirring is continued to obtain the corrosion-resistant hydrophilic easy-to-clean coating.
Citation Information
Patent Citations
Hydrophilic top coating, relevant stainless steel sink and preparation method
CN109439042A
Superspreading wetting agent and preparation method thereof
CN110818890A
Hydrophilic easy-to-clean coating and preparation method and application thereof
CN111040486A
Water-based long-acting anti-fog self-cleaning coating and preparation method thereof
CN115304942A
Photocatalytic self-cleaning water-based pure inorganic coating and preparation method thereof
CN116144203A